2019
DOI: 10.1017/s095457941800158x
|View full text |Cite
|
Sign up to set email alerts
|

Romantic functioning mediates prospective associations between childhood abuse and neglect and parenting outcomes in adulthood

Abstract: Research suggests intergenerational links between childhood abuse and neglect and subsequent parenting quality, but little is known about the potential mechanisms underlying intergenerational continuities in parenting. Adult romantic functioning may be one plausible mechanism, given its documented associations with both adverse caregiving in childhood and parenting quality in adulthood. The present study used data from the Minnesota Longitudinal Study of Risk and Adaptation to (a) investigate prospective assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 73 publications
0
18
1
Order By: Relevance
“…Interestingly, there was no main effect of parent’s CM exposure on the exposure to physical violence in adulthood. This differs from studies showing that parent’s CM experiences predict IPV in adulthood (Adams et al, 2019; Labella et al, 2019; Miranda et al, 2011, 2013a, 2013b) and the potential for indirect transmission of CM. However, other evidence indicates that child abuse potential is increased if the mother has IPV-related PTSD (Anderson et al, 2018).…”
Section: Discussioncontrasting
confidence: 92%
“…Interestingly, there was no main effect of parent’s CM exposure on the exposure to physical violence in adulthood. This differs from studies showing that parent’s CM experiences predict IPV in adulthood (Adams et al, 2019; Labella et al, 2019; Miranda et al, 2011, 2013a, 2013b) and the potential for indirect transmission of CM. However, other evidence indicates that child abuse potential is increased if the mother has IPV-related PTSD (Anderson et al, 2018).…”
Section: Discussioncontrasting
confidence: 92%
“…For instance, healthy or disrupted attachment relationships with primary caregivers beginning in infancy have well-documented, long-term effects on relationships into adulthood (Sroufe et al 2009; Booth-LaForce and Roisman 2014). A large body of research on early experiences has also documented associations between childhood abuse, neglect, and other interpersonal adversities (e.g., exposure to parental domestic violence and household discord) and adulthood problems in the domains of physical and mental health, romantic relationships, and parenting (Belsky, Conger, and Capaldi 2009;CDC 2019a;Felitti et al 1998;Labella et al 2019;Narayan et al 2014;Narayan, Englund, and Egeland 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Research in this Special Section by Adams, Handley, Manly, Cicchetti, and Toth (2019), Augustyn, Thornberry, and Henry (2019), Capaldi, Tiberio, Pears, Kerr, and Owen (2019), Choi et al (2019), Pittner et al (2019), and St-Laurent, Dubois-Comtois, Milot, and Cantinotti (2019) focus specifically on maltreatment as an outcome. In particular, Labella, Raby, Martin, and Roisman (2019) test effects on both parenting problems and maltreatment and Narayan, Ippen, Harris, and Lieberman (2019) investigate children's trauma exposure (which included child maltreatment) as an outcome. Moreover, Oosterman, Schuengel, Forrer, and De Moor (2019) and Zajac, Raby, and Dozier (2019) investigate mechanisms underlying the association between a history of experiencing maltreatment and parenting problems, such as parenting self-efficacy, harsh discipline, and parental (in)sensitivity.…”
Section: A Continued Search For Mechanismsmentioning
confidence: 99%
“…Using a similar perspective, Capaldi et al (2019) found no evidence for delinquency or substance use as mediating mechanisms of the transmission of physical maltreatment specifically; however, the relation between severe experienced maltreatment and adulthood delinquency was significant. Adams et al (2019) and Labella et al (2019) found support for partner relationship problems (romantic competence and relationship violence) as a mechanism of the effect of experienced maltreatment on (lack of) supportive parenting (Labella at al., 2019) and perpetrated maltreatment (Adams et al, 2019; Labella at al., 2019). Zajac et al (2019) showed that in families involved with Child Protective Services, dismissing and unresolved attachment states of mind based on the Adult Attachment Interview were related to sensitivity, but childhood maltreatment experiences were not significantly related to sensitivity.…”
Section: A Continued Search For Mechanismsmentioning
confidence: 99%